STRATEGIES TO IMPROVE THE EMPLOYEE SATISFACTION AT ISLAMIC RURAL BANK IN LAMPUNG, INDONESIA - Nurul Hida Yati; Ruslan Abdul Ghofur; Erike Anggraeni (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2020)
This study aims to describe the strategy of increasing job satisfaction employees of the Islamic Rural Bank in Lampung, Indonesia through Islamic leadership and work ethics. The approach used in this study is descriptive verification research using survey methods. The population of this study was Islamic Rural's Bank, which amounted to 11 Islamic Rural's Financing Bank. Data were obtained by using questionnaires given to employees of two banks which were the samples of the study, namely Islamic Rural Bank Kotabumi and Islamic Rural Mitra Agro Usaha with a total sample of 43 employees. Data were analyzed using linear regression analysis. Based on the results of the study successfully proved that, "The leadership style and Islamic work ethics have a significant influence partially (t test) and simultan (f test) on employee job satisfaction." Keywords: Islamic banks, leadership, ethics, satisfaction